Alcohol investment policy in Indonesia according to Maqasid Shariah - Aris Anwaril Muttaqin; Muhammad Adib Samsudin; Ahmad Dahlan Salleh; Azlin Alisa Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Investments which are considered beneficial for the economy have caused controversy in the Indonesian society when the government enacted the Peraturan Presiden Nomor 10 Tahun 2021, which contains an article on alcohol-related investments. This study analysed the relationship between government policies and public figure responses relating to alcohol-related investments in Indonesia based on the Maqasid Shariah approach. This study used content analysis methodology and data were obtained by analysing documents, online media information and check lists. Two experts in Islamic Economics were involved and Cohen’s Kappa test was used to measure inter-rater reliability for qualitative (categorical) items, which yielded a score of 1 for each expert. Study data analysis was carried out descriptively and thematically. Findings show that policies to encourage investments considered beneficial for the economy have in fact, harmed the Indonesian society in general because the policies are contrary to the principles of Maqasid Shariah. The Muslim society believes that alcohol investments are detrimental to the country. The implications appear in the form of policies contradicting the maslahah (public interest) of the society, public rejection of investment policies, and rescinding of the government’s investment policies. Therefore, this study recommends that governments, in this case Indonesian government, should consider the Maqasid Shariah principles when formulating policies, especially those concerning the wider community, in the future.